Silencing of Glucocerebrosidase Gene in Drosophila Enhances the Aggregation of Parkinson's Disease Associated α-Synuclein Mutant A53T and Affects Locomotor Activity - Abul Khair, Salema B.; Dhanushkodi, Nisha R.; Ardah, Mustafa T.; Chen, Wenfeng; Yang, Yufeng; Haque, M. Emdadul (Frontiers in Neuroscience, 2018)
Background: Mutations in glucocerebrosidase (GBA), a lysosomal enzyme are the most common genetic risk factor for developing Parkinson's disease (PD). We studied how reduced GCase activity affects α-synuclein (α-syn) and its mutants (A30P and A53T) aggregation, neurodegeneration, sleep and locomotor behavior in a fly model of PD. Methods: We developed drosophila with GBA gene knockdown (RNAi) (with reduced GCase activity) that simultaneously expresses either wildtype (WT) or mutants such as A30P or A53T α-syn. Western blot and confocal microscopy were performed to study the α-syn aggregation and neurodegeneration in these flies. We also studied the sleep and locomotor activity of those flies using Drosophila activity monitor (DAM) system. Results: Western blot analysis showed that GBA RNAi A53T α-syn flies (30 days old) had an increased level of Triton insoluble synuclein (that corresponds to α-syn aggregates) compared to corresponding A53T flies without GBA RNAi (control), while mRNA expression of α-syn remained unchanged. Confocal imaging of whole brain staining of 30 days old drosophila showed a statistically significant decrease in neuron numbers in PPL1 cluster in flies expressing α-syn WT, A30P and A53T in the presence GBA RNAi compared to corresponding control. Staining with conformation specific antibody for α-syn aggregates showed an increased number of neurons staining for α-syn aggregates in A53T fly brain with GBA RNAi compared to control A53T flies, thus confirming our protein analysis finding that under decreased GBA enzyme activity, mutant A53T aggregates more than the control A53T without GBA silencing. Sleep analysis revealed decreased total activity in GBA silenced flies expressing mutant A53T compared to both A53T control flies and GBA RNAi flies without synuclein expression. Conclusion: In A53T flies with reduced GCase activity, there is increased α-syn aggregation and dopamine (DA) neuronal loss. This study demonstrates that reduced GCase activity both in the context of heterozygous GBA1 mutation associated with PD and in old age, contribute to increased aggregation of mutant α-syn A53T and exacerbates the phenotype in a fly model of PD.